Analysis of the Effectiveness Value of the Coconut Fiber (Cocos nucifera L) Absorption Coefficient as a Sound Dampener - Nurjannah, Indra; Rahmawati, Eka Septia; Habibah, Habibah; Nuryadin, Atin; Subagiyo, Lambang; Haryanto, Zeni (Journal BEARINGS: Borneo Mechanical Engineering and Science, 2024)
In this modern era, noise has become an increasingly common and significant problem in everyday life, thus requiring the use of sound absorbers to address this noise issue. This research created a sound absorber using coconut husk waste through the impedance tube method. Sound absorbers can be made by utilizing readily available waste materials, such as coconut husk waste. The effectiveness value of the coconut fiber absorption coefficient was tested using the impedance tube. The research method employed was the impedance tube method, with variations ranging from level 1 to level 5 and frequencies of 200 Hz, 400 Hz, 600 Hz, and 800 Hz. The impedance tube lengths used in this study were 50 cm and 100 cm. The highest absorption result at a tube length of 50 cm was found at level 1 with a frequency of 200 Hz. At a tube length of 100 cm, the highest absorption value was observed at level 2 with a frequency of 600 Hz. Based on this research, it was concluded that coconut husk can minimize noise and serve as an effective sound absorber.